ANALISIS PENGUKURAN KINERJA RUMAH SAKIT DENGAN PENDEKATAN BALANCED SCORECARD (Studi Kasus Pada RSUD Prof. Dr. Soekandar Mojosari) - Utama, Nizar Alif; Hariadi, SE., M.Ec., Ak., Bambang (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
RSUD Prof. Dr. Soekandar is a government-owned hospital whose primary purpose is to provide social function in delivering health services for society. As one of the government institution, RSUD Prof. Dr. Soekandar should be able to provide performance measurement both financial and non-financial to local government and society as service users. Therefore, it is necessary to measure non-financial aspects instead of measuring financial aspects only. This research aims to measure the performance of RSUD Prof. Dr. Soekandar according to four persepectives of balanced scorecard, consisiting of: financial perspective, customer perspective, internal business perspective and leraning & growth perspective. This research was conducted by collecting datas for three years, from 2009 to 2011. Comparative analysis used in this research to evaluate hospital performance between periods. While to analyze customer and learning & growth perspective, researcher using the calculation’s result of questionnaires that distributed to customer (patient) and employees of RSUD Prof. Dr. Soekandar. The hospital performance measurement results show that the overall performance of RSUD Prof. Dr Soekandar is good enough seen from four perspectives of balanced scorecard. Keywords: Balanced Scorecard, Financial Perspective, Customer Perspective, Internal Business Process Perspective, Learning and Growth Perspective